Safety and efficacy of a modified endoscopic full-thickness resection technique for gastric submucosal tumors: a case series - Zhou, Yingsheng; Huang, Yan; Cheng, Wen; Wang, Jiamin; Liu, Xiaoqiang; Peng, Huan; Zhang, Juan; Feng, Qiaoqun (Frontiers in Oncology, 2024)
Objectives Endoscopic full-thickness resection (EFTR) has proven effective and economical for patients with gastric submucosal tumors (SMTs). However, the poor operative field of view, the risk of massive hemorrhage, and the difficulties in defect closure have limited its widespread application. Herein, we described a modified EFTR technique developed to simplify the dissection and defect closure procedures using common and economical endoscopic accessories. Methods Forty-two patients who underwent the modified EFTR for gastric SMTs in the Shenzhen Guangming District People’s Hospital were enrolled in the case series. Following a cross incision to expose the intraluminal surface the tumors were captured by suction through a transparent cap and the roots were ligated using a loop. The tumors and part of the suction tissue were removed along the ligated root. A tension-relieving closure was performed by clipping the raised plica in four quadrants outside the ligated root. Patient demographics, tumor characteristics, and therapeutic outcomes were evaluated retrospectively. Results All tumors had an R0 resection. The median procedure time was 51.8 min (IQR 34.25 min). No severe perioperative adverse events occurred. No residual lesion or recurrence was reported during the follow-up period of 9.84 months (IQR 5.0 months). Conclusion The safety and practicability of Modified-EFTR could allow for wide clinical application in patients with micro-gastric SMTs.